Solitary plasmacytoma of bone and extramedullary plasmacytoma - Dimopoulos, M.A.; Kiamouris, C.; Moulopoulos, L.A. (Hematology/Oncology Clinics of North America, 1999)
A small proportion of patients with plasma cell myeloma have a solitary plasmacytoma of bone. Strict staging criteria, including normal MR imaging studies of the axial skeleton and the long bones and absence of monoclonal plasma cells detected by flow cytometry or PCR, are required for diagnosis. Radiotherapy at a dose of 4500 cGy is required to eradicate the local tumor. Many patients enjoy prolonged disease-free survival, but the incidence of systemic relapse is high. It is expected, however, that if strict diagnostic criteria are applied some patients may be cured. Extramedullary plasmacytoma is an even rarer plasma cell disease which usually occurs in the head and neck area. Careful microscopic and immunohistochemical studies are required for the correct diagnosis, because this disease can be confused with other malignancies, particularly lymphomas. The treatment of choice is radiotherapy which, in cases of head and neck plasmacytomas, should encompass the adjacent lymph nodes. Most patients with extramedullary plasmacytoma can be cured, and fewer than 30% develop a distant failure in the form of multiple myeloma or multiple extramedullary tumors.